Alterations of immunoendocrine responses during the recovery period after acute prolonged cycling - Li, T. L.; Cheng, P. -Y. (European Journal of Applied Physiology, 2007)
The aim of this study was to determine the timecourse of recovery of immunoendocrine responses following prolonged cycling. With the approval of the Ethics Committee, ten healthy men (age 21.6 ± 0.9 years, height 1.77 ± 0.01 m, body mass 66.9 ± 1.8 kg, VO2max 54.2 ± 2.0 ml kg-1 min-1; means ± SEM) performed either a 2 h cycling trial at 55% peak aerobic power or a resting control trial in a counterbalanced order, separated by at least 6 days. No food was consumed, though water ingestion was allowed ad libitum, until trials were completed. Venous blood samples were collected at pre-exercise, post-exercise, and at 1, 3, 6 and 9 h post-exercise. Haematological analysis was performed using an automated cell counter. Plasma concentrations of hormones were determined using ELISA kits. Neutrophil degranulation (bacteria-stimulated) and oxidative burst (formyl-methionyl-leucyl-phenylalanine-induced) were measured using an ELISA kit and a chemiluminescence assay, respectively. Results were analyzed using two-factor repeated measures ANOVA with post hoc Tukey tests and paired t tests applied where appropriate. The main findings of this study were that, compared with the resting trial, an acute single bout of prolonged exercise (1) decreased plasma glucose concentrations but increased circulating leukocyte, neutrophil, and monocyte counts for 9 h; (2) increased plasma cortisol concentrations but suppressed neutrophil function on a per cell basis for 6 h. In conclusion, the findings of this study suggest that the impact of a single bout of prolonged cycling on immunoendocrine responses would be recovered around 9 h post-exercise at fasted status.